Global investment trends and prospects of Ukraine's investment attractiveness - Tikhonova, Nataliia; Klymash , Nataliia (Ways to Improve Construction Efficiency, 2025)
The article is devoted to the study of the main global investment trends of 2024–2025 and the specifics of their impact on global economic processes. The research analyzes the key reasons for the transformation of investment flows, summarizes and systematizes statistical data from authoritative international and national sources, and identifies the leading trends and promising directions for the development of investment activities on a global scale. Separate attention is paid to the growing role of sustainable investment approaches, in particular the ESG concept, as well as to the development of the digital economy as one of the defining factors of modern investment processes. The article emphasizes the importance of achieving proven environmental and social outcomes of investment projects and ensuring transparent and effective corporate governance, which significantly affects the level of trust on the part of investors. It also highlights the increasing share of the digital economy in the structure of global investment, driven by the rapid development of digital services, rising demand for software products, and the introduction of innovative technologies across various sectors. The main directions of economic digitalization are identified, and special attention is focused on the fact that the combination of technological solutions with sustainable practices significantly enhances investor interest in agribusiness. A separate section of the article is devoted to the analysis of investment processes in Ukraine. The most promising sectors for increasing the country’s investment attractiveness are outlined, and it is noted that Ukraine possesses significant competitive advantages, particularly in the agricultural sector. At the same time, it is emphasized that the level of investment inflows largely depends on political stability, the pace of reforms, economic modernization, and the ability to effectively attract and utilize international financial instruments. The article also identifies the key risks that currently restrain potential investors when considering the implementation of investment projects related to Ukraine.